Influencing factors of home exercise adherence in elderly patients with stroke: A multiperspective qualitative study - Zhang, Yuanxing; Qiu, Xichenhui; Jin, Qiansheng; Ji, Cuiling; Yuan, Ping; Cui, Mengjiao; Zhang, Juanjuan; Chen, Lu (Frontiers in Psychiatry, 2023)
Introduction Evidence has shown that stroke exercise rehabilitation is the most effective way to improve disease prognosis, but home exercise adherence in elderly patients with stroke is low due to they are more likely to have movement disorders, cognitive disorders, mental disorders, etc. Currently, most studies on exercise adherence in elderly patients with stroke are quantitative, and there is a lack of qualitative studies from the perspective of patients, caregivers, and medical staff. Considering the importance of home exercise adherence in elderly patients with stroke, the present study aimed to explore the influencing factors of home exercise adherence in them and summarize the potential ways to improve it. Methods From October to December 2022, 9 medical staff, 12 elderly patients with stroke and 7 caregivers from a level A tertiary hospital and community health service center in Nanjing, Jiangsu Province were selected by the purposive sampling and were interviewed in a face-to-face semi-structured way. The data were analyzed and summarized by the phenomenological analysis of Colaizzi’s method. Results The influencing factors of home exercise adherence in elderly patients with stroke can be summarized into 3 themes and 8 subthemes. These were individual factors (physical impairment, exercise self-efficacy, and depression), family factors (caregiving ability and emotional support); and stroke rehabilitation environment (exercise prescription, monitoring and feedback, and organizational policy). Conclusion Home exercise adherence in elderly patients with stroke was influenced by many factors. Medical staff should assess the patient’s physical function and depression, establish a multi-support system, formulate personalized exercise prescription, pay attention to the monitoring and feedback of home-based exercise rehabilitation, and improve the home-based rehabilitation model for stroke, so as to improve the home exercise adherence in elderly patients with stroke and promote the best rehabilitation effect.